PERSEPSI PARA USTADZ PONDOK AL-MUHSIN TENTANG BUNGA UANG TERHADAP MODAL USAHA - Tarmizi, Tarmizi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
ABSTRACTLegal issues interest money is a long time until is still being debated and still warmÂ Â Â (up to date) to be studied. Venture capital can be obtained through their own funds or from loans either flowering or without interest. Equity and interest-free loans hard to come by smaller and refund period is shorter than that of capital loans . This leads to people / companies prefer to raise capital through loans. Quran did not give an explanation interest money, but included in the study usury. The scholars of diverse opinions on the legal interest as working capital. This research is aimed at exploring the perceptions of the cleric Al-Muhsin cottage on the interest money as venture capital. The results showed that the cleric Pondok Pesantren Al - Muhsin different opinions about the legal interest of money as capital. In this case can be classified in two kinds. First, unclean sponsored by teachers, teacher interpretation, hadith, and the opinions of teachers, teacher sayariah/fiqh and religious scholar, teacher of Islamic dates. Second, permissible, sponsored by the opinions of teachers, teacher syariah/ Date fiqh and Islamic cleric opinion, and the opinion of the chaplain/ language teach.Â Key words: Interest money, venture capital, haraam, revenue sharing system, the cleric Â Â PondokPesantren Al â Muhsin.Â